2018
DOI: 10.1002/gps.4844
|View full text |Cite
|
Sign up to set email alerts
|

Measuring anticholinergic exposure in patients with dementia: A comparative study of nine anticholinergic risk scales

Abstract: There is a large difference in outcomes among the 9 anticholinergic risk scales. Clinicians and researchers should be aware of these differences when using these instruments in patients with dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 42 publications
2
12
1
Order By: Relevance
“…In the identification of anticholinergic prescriptions prior to fracture, the greatest consistency was found between the ADS and ACB scales (high: 71%), which was also evident in three other studies but in different clinical contexts (62% and 65% in patients with general illness in the US and Australia, respectively, and 62% in patients with dementia in Spain) [19,20,22]. The lowest consistency was observed between the ADS and ARS scales (moderate: 48%), differing from that reported in the other studies, where the poorest agreement was observed between the ACB and ARS scales (20%, 24% and 43%) [19,20,22]. In those studies, the consistency between ADS and ARS was 26% [19], 31% [22] and 53% [20].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In the identification of anticholinergic prescriptions prior to fracture, the greatest consistency was found between the ADS and ACB scales (high: 71%), which was also evident in three other studies but in different clinical contexts (62% and 65% in patients with general illness in the US and Australia, respectively, and 62% in patients with dementia in Spain) [19,20,22]. The lowest consistency was observed between the ADS and ARS scales (moderate: 48%), differing from that reported in the other studies, where the poorest agreement was observed between the ACB and ARS scales (20%, 24% and 43%) [19,20,22]. In those studies, the consistency between ADS and ARS was 26% [19], 31% [22] and 53% [20].…”
Section: Discussionsupporting
confidence: 58%
“…However, there is considerable variation among the anticholinergic burden scales, especially in terms of antimuscarinic potency and the number of drugs considered in each instrument [16,17], and there is no current consensus on which scale is optimal [18]. There are few studies that have compared the agreement between anticholinergic burden scales, which have shown in several clinical contexts generally low or intermediate consistencies [19][20][21][22]; moreover, it is unknown which scale identifies the highest proportion of anticholinergic drugs in patients with fractures and the variability or agreement between the instruments is unknown, especially since some of the drugs considered in the risk scales are not available in all countries. Therefore, the aim of this study was to identify the degree of agreement between the anticholinergic burden scales in patients diagnosed with fracture in Colombia.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is considerable variation among the anticholinergic burden scales, especially in terms of antimuscarinic potency and the number of drugs considered in each instrument, and there is no current consensus on which scale is optimal . There are few studies that have compared the agreement between anticholinergic burden scales . Oriol et al ., in patients with a diagnosis of dementia, compared the different anticholinergic load scales and found that the Anticholinergic Cognitive Burden Scale identified the highest proportion of anticholinergic drugs among the most validated instruments …”
Section: Discussionmentioning
confidence: 99%
“…There are few studies that have compared the agreement between anticholinergic burden scales . Oriol et al ., in patients with a diagnosis of dementia, compared the different anticholinergic load scales and found that the Anticholinergic Cognitive Burden Scale identified the highest proportion of anticholinergic drugs among the most validated instruments …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation